Discourse with Media Practitioner - Dato’ Chamil Wariya: “Kewartawanan Media di Malaysia: Menoleh ke Belakang, Memandang ke Depan” - Jamali Bujang, Sanawi (Faculty of Engineering, 2014)
On the 26 November 2014, Department of Communication, FSS had organized a talk entitled “Kewartawanan Media di Malaysia: Menoleh ke Belakang, Memandang ke Depan” with Dato’ Chamil Wariya, a renowned media practitioner in Malaysia as its guest of honor and speaker. Dato’ Chamil Wariya has vast experience in media industry and he had published five books related to journalism. He also interested in local politic in which he had published more than 30 books on that subject. He is currently the Chief Executive Officer at Malaysia Press Institute (MPI). During the talk, Datuk Chamil highlighted some of the issues pertaining to journalism in Malaysia and how readers should be more critical and creative in their quest for information. He also shared some of his experiences in media industry in and out of Malaysia. Through out his 38 years in the industry, he summed it up as a ‘sweet’ experience. Apart from that, Datuk Chamil also addressed several questions from the audience with most of them interested to know more about career in media industry and how to become prominent in that field. At the end of the talk, Datuk Chamil contributed two of his books to the faculty.